Assessing manure availability and utilization in integrated crop-livestock system: implications for nitrogen management in rural Eastern Cape, South Africa - Admire R. Dzvene; Cornelius Chiduza; Pearson N. S. Mnkeni (Discover Agriculture)
Abstract Animal manure is a valuable organic resource of nitrogen (N) for crops, but it can also be a potential source of environmental pollution, depending on how it is managed and utilized at the farm level. Whilst manure is commonly used as an organic fertilizer amendment in crop production in many smallholder farming systems in southern Africa, this is not necessarily the case in South Africa. The objective of this study was to investigate and evaluate the productivity of crop and livestock components. The study focused on the quantities of manure production and its utilization as N source in croplands using a case study of the Eastern Province Cape, which typifies smallholder rural South Africa. A purposive random sampling of one hundred and fourteen households in the Raymond Mhlaba Local Municipality was interviewed using semi-structured questionnaires. The households practice an integrated crop-livestock system, in which livestock rearing is the dominant diversified component, with 69.3% of the households raising more than one type of animal. The majority (78.7%) of farmers with access to communal arable land had outfields with land sizes ranging from 0.6 to 2 hectares (ha). Only 35.1 and 22.8% of households used manure and processed it before applying it to crop fields as N fertilizer. The overall quantities of manure utilized in crop fields amounted to 515 t, and manures that remained unutilized were 4367 t. The findings of this study show the weak linkage between the crop and livestock enterprises regarding manure use. The underutilization of manure and its impacts on the environment requires further study to assist in defining sustainable management practices for this and similar smallholder environments.